2008
DOI: 10.1007/s10639-008-9079-3
|View full text |Cite
|
Sign up to set email alerts
|

Training with ICT for ICT from the trainee’s perspective. A local ICT teacher training experience

Abstract: The introduction of ICT (Information and Communication Technologies) presents new challenges for teachers and often meets with their belief that ICT, as well as other changes present a factor, which can cause several changes in school. Although there have been many education reforms regarding teachers' training policy in recent years and the number of training programs has been increased, they have not been able to satisfy teachers' needs to a substantial degree. In this research the results from an explorator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 15 publications
0
59
0
6
Order By: Relevance
“…Findings of existing research Ertmer et al, 2012;Kalogiannakis, 2008) confirmed that there is a relationship between teachers' readiness to use technology and years of teaching experience. However, the literature reveals unclear and contradictory results.…”
Section: Factors Affect Teachers' Readiness To Adopt Technologymentioning
confidence: 77%
“…Findings of existing research Ertmer et al, 2012;Kalogiannakis, 2008) confirmed that there is a relationship between teachers' readiness to use technology and years of teaching experience. However, the literature reveals unclear and contradictory results.…”
Section: Factors Affect Teachers' Readiness To Adopt Technologymentioning
confidence: 77%
“…To illustrate, in a study of innovative ICT usage in secondary schools in the UK, three key themes emerged: in addition to the need to incorporate new pedagogies when using new technologies and the use of these innovations for school public relations, the study highlighted the changing roles of teachers (Pearson & Naylor 2006). The changing roles of teachers were a factor in teachers expressing the need for in-service training programs concerning the pedagogical use of ICT in class practice in a recent Greek case study (Kalogiannakis 2010). According to additional research literature, introducing ICT for educational purposes requires balance between vision for ICT use and other aspects of educational activity (Vanderlinde, Aesaert & Van Braak 2014).…”
Section: 1mentioning
confidence: 99%
“…However, studies show that there is a gap between the courses that preschool teacher candidates took about ICT in university education and the expected level of ICT use in preschool education environments (Kalogiannakis, 2010). Basic computer skills underlie the ICT literacy, but this isn't enough for the preschool teachers to insert them in ICT educational processes (Wetzel, Wilhelm & Williams, 2004).…”
Section: Technology In Preschool Education By Preschool Teachersmentioning
confidence: 99%
“…Teaching profession also requires the development of a pedagogical role by not only being limited to teaching a new course. Teachers are required to change their pedagogical role if they want to use new methods and technologies (Kalogiannakis, 2010). Information and communication technologies (ICT) are the leading technologies that will cause to this change.…”
Section: Introductionmentioning
confidence: 99%